2013
DOI: 10.1530/joe-13-0279
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroid monkeys: a nonhuman primate model of experimental Graves' disease

Abstract: Graves' disease (GD) is a common organ-specific autoimmune disease with the prevalence between 0.5 and 2% in women. Several lines of evidence indicate that the shed A-subunit rather than the full-length thyrotropin receptor (TSHR) is the autoantigen that triggers autoimmunity and leads to hyperthyroidism. We have for the first time induced GD in female rhesus monkeys, which exhibit greater similarity to patients with GD than previous rodent models. After final immunization, the monkeys injected with adenovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Subgroup analysis based on different types of AITD indicated that the proportion of circulating Tregs was lower in untreated GDs than in HCs, which is in accordance with previous studies that revealed a significantly lower percentage of Tregs in female rhesus monkeys with GD [32]. When Tregs were depleted, both disease incidence in resistant C57BL/6 mice and disease severity in susceptible BALB/c mice were enhanced [33].…”
Section: Discussionsupporting
confidence: 89%
“…Subgroup analysis based on different types of AITD indicated that the proportion of circulating Tregs was lower in untreated GDs than in HCs, which is in accordance with previous studies that revealed a significantly lower percentage of Tregs in female rhesus monkeys with GD [32]. When Tregs were depleted, both disease incidence in resistant C57BL/6 mice and disease severity in susceptible BALB/c mice were enhanced [33].…”
Section: Discussionsupporting
confidence: 89%
“…H2 h4 mice is the restoration of tolerance to the TSHR. Methods used to induce hyperthyroidism in mice, unsuitable for inducing self-tolerance to the TSHR, include: TSH injection (for example 48), TSAb mAb injection (45), hamster TSAb mAb hybridoma injection (44), TSHR immunization approaches to express TSHR in mice (59), hamsters (10) and rhesus monkeys (11), and expressing TSAb (B6B7) in a transgenic mouse (42,43). Confounding effects of hyperthyroidism on the immune system include altering the phenotype and function of antigen-presenting dendritic cells (46) and polarizing dendritic cells leading to impaired function of regulatory T-cells (Treg), a major change that may influence the emergence of pathogenic autoantibodies (47).…”
Section: Figurementioning
confidence: 99%
“…In 1996, a breakthrough occurred with the demonstration that in vivo expression of the TSHR was necessary to induce thyroid stimulating antibodies (TSAb) in mice, with resultant hyperthyroidism (4). Subsequently, different vectors and immunization approaches have been used to express TSHR in vivo leading to TSAb induction and hyperthyroidism, for example in some mouse strains (59), hamsters (10) and rhesus monkeys (11). …”
Section: Introductionmentioning
confidence: 99%
“…Effects of Ad-TSHR immunisation were reported in three rhesus macaque monkeys which were successfully treated with seven consecutive injections over 20 weeks [29]. Clinical investigation of these three animals also indicated increased heart rate (no details on method were given).…”
Section: Cardiac Involvement In Animal Disease Models Of Graves’ Diseasementioning
confidence: 99%